PROFIL PENGOBATAN KEMOTERAPI PADA PASIEN KANKER PAYUDARA DI RUMAH SAKIT UMUM DAERAH KOTA BOGOR PADA TAHUN 2022 - Anjani Dwi Cahya; Halimatushadyah, Ernie; sari, Dwi Puspita; Ekasari, Dian (Jurnal Riset Kefarmasian Indonesia, 2024)
Breast cancer is cancer that starts in the breast tissue, which consists of milk-producing glands (lobules) and ducts that connect the lobules to the nipple. One of the efforts to reduce the morbidity rate of breast cancer is chemotherapy. Chemotherapy involves the use of cytostatic drugs aimed at stopping the growth and spread of cancer cells. The purpose of this study was to determine the pattern of drug use and evaluation of drug use in breast cancer patients. The study was conducted observational with retrospective data collection. The research was conducted from May to June 2023. The number of samples was 96 samples with the method of purposive sampling technique using the slovin formula, the data were analyzed qualitatively. The results of the chemotherapy treatment profile using single therapy 9 patients (9.38%), combination therapy 87 patients (90.63%) with a combination chemotherapy regimen of Epirubicin and Cyclophosphamide followed by Paclitaxel as many as 50 patients (57.47%). Evaluation of appropriate patient (98.96%), appropriate indication (100%), appropriate drug (100%), appropriate dose (19.79%), inappropriate dose (20.83%), under dose (34.48%), over dose (25%).